Research progress and clinical application of all-inside reconstruction techniques: narrative review - Jiang, Yong; Qian, Dikun; Lu, Qiming; Cao, Yangbin; Ren, Yi; Su, Jun (Frontiers in Surgery, 2025)
All-inside reconstruction is a popular technique for cruciate ligament reconstruction in recent years. Compared with traditional reconstruction techniques, all-inside reconstruction is primarily performed through minimally invasive arthroscopic procedures, involving the creation of separate half-tunnels at the femoral and tibial ends, followed by fixation of the graft using adjustable suspension devices to achieve anatomical ligament reconstruction. Current research primarily focuses on anterior cruciate ligament (ACL) reconstruction in the knee joint, demonstrating advantages such as reduced surgical trauma, bone preservation, decreased postoperative pain, and accelerated rehabilitation. Extensive clinical studies have shown that all-inside reconstruction achieves comparable mid- to short-term clinical outcomes to traditional techniques, with superior performance in certain functional metrics. Additionally, all-inside reconstruction is associated with lower complication rates, smaller incisions that better preserve tendons, and reduced postoperative pain and discomfort. However, the technique also has limitations, such as a steep learning curve, potential graft micromotion due to suspension fixation, and tunnel widening. Therefore, this review aims to comprehensively elaborate on the developmental history, principles, applications across various joints, perioperative management, postoperative rehabilitation, efficacy evaluation, and biomechanical research outcomes of all-inside reconstruction. It will also discuss the clinical advantages and limitations based on the latest clinical studies, as well as future directions for improvement and research prospects.